MOLECULAR IDENTIFICATION OF GIARDIA LAMBLIA GENOTYPES ISOLATES FROM CHILDREN WITH DIARRHEA (Iraqi Journal of Medical Sciences, 2016)
Background:Infection with Giardia lamblia (G. lamblia) parasite regarded as the most important causative agent for diarrhea, and a major public health problem.Objectives:Molecular identification and characterization of G. lamblia genotypes and association with gender, age and presence of different clinical signs.Methods:One hundred children with diarrhea were included. Fecal samples were taken from them during the period from May 2014 to February 2015. The age range was 2 months to 18 years. All stool samples were examined by microscopic examination, multiplex real time polymerase chain reaction and nested PCR.Results:Among 42 fecal samples from patients with giardiasis diagnosed by multiplex real time PCR, amplification of triosphosphate isomerase gene of G. lamblia was successful among 25/42 (59.52%) samples. However, the amplification of these samples showed that 7 (28%) contained genotype A and 18 (72%) samples contained genotype B; genotype B was more prevalent than A in males 11/18 (61.11%) and females 7/18 (38.89%) respectively. Regarding age, the results showed that no differences in distribution of genotypes were found statistically among different age groups of patients. Regarding to clinical aspects, the rates of abdominal pain, weight loss, anorexia and fever of giardiasis genotype B are higher than the genotype A.Conclusion:G. lamblia genotype B is the most frequent genotype among children with diarrhea. Also, the presence of the clinical aspects is genotype specific.Keywords: Giardia lamblia, children with diarrhea, and molecular identification.